Endomicroscopy Will Track Injected Mesenchymal Stem Cells in Rat Colitis Models. Issue 9 (September 2015) - Li, Ming; Zhang, Yi-Xin; Zhang, Zhen; Zhou, Xiao-Yan; Zuo, Xiu-Li; Cong, Yingzi; Li, Yan-Qing
Abstract : Background: Mesenchymal stem cells (MSCs) have demonstrated significant potentials for the treatment of inflammatory bowel disease. Clinical feasible methods to individually document the MSC recruitment to intestinal mucosa is lacking. Here, we proposed that endomicroscopy could noninvasively track MSCs in vivo at cellular resolution. Method: Isolated Sprague Dawley rat MSC was characterized, fluorescently labeled, and imaged ex vivo using an endomicroscope. Then enhanced green fluorescent protein (eGFP)-labeled MSC was tracked in vivo, and acquired images were compared with immunofluorescence, immunohistology, and fluorescent in situ hybridization results. Results: Endomicroscopy visualized clearly the eGFP-labeled or carboxyfluorescein succinimidyl ester–stained MSC ex vivo. Endomicroscopy using the FIVE1 system could track eGFP-labeled MSC with distinct in vivo features. Immunofluorescence, immunohistochemistry, and fluorescent in situ hybridization confirmed the presence of eGFP-positive cells. In vivo endomicroscopy could quantify the transplanted MSCs that homed to colonic mucosa of the recipient rat in multiple models, including the rat-to-rat allograft, human-to-rat xenograft, hypoxia-induced MSC, and busulfan immunosuppressed recipient rat models. After hypoxia induction, there was a trend of enhanced rat MSC homing to the inflamed mucosa as visualized by endomicroscopy (114.1 in hypoxia group versus 34.3 in other 3 groups combined, t = 2.14, P = 0.0644). Conclusions: Endomicroscopy is a novel and promising tool to track transplanted MSCs to the colonic mucosa. This clinical available noninvasive cellular tracking method may provide new insight to individualize each recipient's regimen in the future. Abstract : Article first published online 19 May 2015.Supplemental Digital Content is Available in the Text.